DEVELOPMENT OF INTERACTIVE E-LKPD BASED ON THE R2L METHOD TO IMPROVE STUDENTS’ HOTS SCIENCE LITERACY - Silvia Gressiela Br Sembiring; Iis Siti Jahro (Smart Education, 2025)
Abstract: This research aims to find out data and information about students' needs of Interactive e-LKPD based on the Reading to Learn (R2L) method to improve Students’ HOTS Science Literacy on Reaction Rates; to find out data and information on the level of interactive feasibility of E-LKPD developed; to determine the influence of the interactive implementation of E-LKPD; to determine the level of effectiveness of interactive E-LKPD. This investigation employs a 4D model methodology. Based on questionnaire results 88.2% students’ needs to E-LKPD based on R2L Method. Based on four material expert validators, it was determined that 4.32 of the material had a very valid or feasible, while 87.40% of student responses were rated as